The Relationship between Patient Motivations with Dietary Compliance in Patients Diabetes Mellitus at Haruai Health Center - Pratiwi, Anjar Padmi; Riduansyah, Muhammad; E. M. Gaghauna, Eirene (International Journal of Clinical Inventions and Medical Sciences (IJCIMS), 2021)
One of the risk factors that affect the increase in blood sugar levels in diabetes mellitus is an irregular diet. To prevent this, it is necessary to comply with the diet. In order for patients to comply with diet therapy, self-motivation and external motivation are needed. To determine patient motivation, level of dietary compliance and the correlation between patient motivation and dietary compliance in diabetes mellitus patients at community Haruai.This study used a cross sectional approach. The sample technique was taken 25% of the total population by purposive sampling method, the sample size was 43. The results of this study indicated based on Sperman Rank (Rho) analysis there was a correlation between patient motivation and dietary compliance in diabetes mellitus patients at community Health Center Haruai with a p value of 0,000. There is a positive correlation between motivation and dietary compliance in diabetes mellitus patients, which means that the better the motivation of the patient, the better the dietary compliance is in the diabetes mellitus patient and both have a strong correlation.